PENGARUH PERSEPSI MAHASISWA TENTANG BANK SYARIAH TERHADAP MINAT MENABUNG DI PERBANKAN SYARIAH - Silvia Miftakhur Rakhmah; Sri Wahyuni (Economic Education, University of Jember, 2016)
This study was conducted to determine the effect of students' perceptions of the Islamic Bank for saving interest in Islamic Banking (a case study on the Economics Education student class of 2011 and 2012 FKIP University of Jember). This research is correlational. The area determination method at Economic Education program, University of Jember. Furthermore, the respondent determination method of this research is proportional random sampling. There are 66 students of Economic Education chosen to be the respondent. Data collection methods used consist of methods: questionnaires, interviews, and documentation. This study used editing, processing, and tabulation as data processing technique. The data collection method is inferential analysis / statistics by using simple regression line analysis, variance analysis of the regression line, the F test, the effectiveness of the regression line, and standard error of estimate in a simple regression line. The result of the research showed that there was a significant effect on students' perceptions of variables Islamic Bank against the interest of saving money in the education of students of Islamic Banking in the economy class of 2011 and 2012 FKIP University of Jember, as much as 77.7%. While the remaining 22.3% influenced by other variables in which did not count in this study, among others, of society such as the reference group (family or peers). In conclusion , the students have positive perception and good respond toward Islamic Bank, then the student will have the desire / interest to save money on the Islamic Bank. Conversely, if the perception held by students about Islamic Bank negative / bad, hence the desire to save the student will also be small.